A Multichannel Flexible Optoelectronic Fiber Device for Distributed Implantable Neurological Stimulation and Monitoring. Issue 4 (29th December 2020) - Yu, Jingxian; Ling, Wei; Li, Ya; Ma, Ning; Wu, Ziyue; Liang, Rong; Pan, Huizhuo; Liu, Wentao; Fu, Bo; Wang, Kun; Li, Chenxi; Wang, Hanjie; et al.
Abstract: Optical fibers made of polymeric materials possess high flexibility that can potentially integrate with flexible electronic devices to realize complex functions in biology and neurology. Here, a multichannel flexible device based on four individually addressable optical fibers transfer‐printed with flexible electronic components and controlled by a wireless circuit is developed. The resulting device offers excellent mechanics that is compatible with soft and curvilinear tissues, and excellent diversity through switching different light sources. The combined configuration of optical fibers and flexible electronics allows optical stimulation in selective wavelengths guided by the optical fibers, while conducting distributed, high‐throughput biopotential sensing using the flexible microelectrode arrays. The device has been demonstrated in vivo with rats through optical stimulation and simultaneously monitoring of spontaneous/evoked spike signals and local field potentials using 32 microelectrodes in four brain regions. Biocompatibility of the device has been characterized by behavior and immunohistochemistry studies, demonstrating potential applications of the device in long‐term animal studies. The techniques to integrate flexible electronics with optical fibers may inspire the development of more flexible optoelectronic devices for sophisticated applications in biomedicine and biology. Abstract : A flexible optoelectronic fiber device consisting of a wireless circuit and four plastic optical fibers transfer‐printed with flexible microelectrode arrays is presented. The flexible optoelectronic fibers can be implanted into multiencephalic regions to conduct programmable light stimulation and high‐throughput biopotential sensing. The device may provide a powerful tool for neuroscience and inspire more sophisticated flexible devices with complex functions.